Perspektif Keadilan Dalam Rumah Tangga : Telaah Konsep Adil dalam Poligami Menurut Undang-Undang dan Kompilasi Hukum Islam - Sifa Mulya Nurani (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
Marriage has the goal of benefiting and prospering in life. Marriage is not only crucial to achieving the happiness of human life on earth. In terms of its kinds, marriage has much diversity. However, unions recognized in the Marriage Law and the Islamic Law Compilation are monogamous and polygamous marriages in Indonesia. Polygamy is discussed in Islam, but the government regulates it with stringent regulations regarding practising polygamy. Law Number 1 of 1974 concerning marriage as a positive response to regulating a husband who wants to marry more than one person. Republic of Indonesia Government Regulation No. 9 of 1975 concerning the Implementation of Law No.1 of 1974 concerning Marriage and in the Compilation of Islamic Law, which regulates polygamy and the requirements for polygamy for Muslims. Ideally, the two regulations of Law no. 1/1974 and KHI aim to provide terms and conditions for husbands who want to remarry (polygamy). These provisions aim to minimize the arbitrary attitude of husbands (men) towards wives (women). This provision is also for the creation of a sakinah, mawaddah and warrahmah. Polygamy that occurs around us still ignores the rules of polygamy as above. Most of them practice polygamy only because of the fulfilment of lust, so they often forget and even violate the main principles in Islamic law, namely the realization of justice and benefit.